The biomechanics of the dipteran wing hinge - Page, J (2018)
Dipteran insects include some of the most aerobatic animals on the planet, including species such as drone flies (Eristalis tenax) which are able to hold a steady hover in the face of environmental perturbations before executing rapid and precise manoeuvres. A deep understanding of the mechanisms of wing kinematic control that afford such abilities is vital if we are to emulate these capabilities in our own bio-inspired machines. This thesis makes use of cutting-edge techniques to visualise these mechanisms in unparalleled detail and determine how they function to control the way in which the wings move. My work here begins by documenting the mechanical interaction of two exoskeletal components around the wing hinge that forms the gear change mechanism of dipteran wing kinematic control. I show its effects on the movement of the wings and explain how the mechanism acts to bring about these changes in Calliphora vicina and E. tenax. I then move on to study another enigmatic structure near the wing hinge, the Pterale C, and argue against a role of this component in mechanically altering wing movement. Instead, I conclude that the Pterale C may be a sensory structure which informs the insect's central nervous system of the position and speed of the wing during the latter half of the downstroke. Finally, I utilise time-resolved synchrotron X-ray computed microtomography to visualise the internal musculature of C. vicina during flight, where I assert that several muscles influence wing movements by restricting the motion of wing hinge components. Throughout this thesis, the inhibition of wing motion and energy absorption pervades each mechanism. Through the application of our understanding of dipteran flight, it may be possible to design bio-inspired machines which begin to approach the aerial capabilities of these insects.